2016
DOI: 10.53761/1.13.1.6
|View full text |Cite
|
Sign up to set email alerts
|

“Bush Law 101”: Realising Place Conscious Pedagogy in the Law Curriculum

Abstract: In 2012, a team of academics from six universities worked on an OLT-funded project, ‘Rethinking Law Curriculum: developing strategies to prepare law graduates for practice in rural and regional Australia’. The project was motivated by the declining proportion of lawyers being attracted to and remaining in practice in rural and regional Australia. The main outcome of the project was an open education resource designed to sensitise students to the realities of the rural and regional legal practice context in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hargreaves (2016), for example, discussed the critical importance of reflection and reflective practice in the context of medical education, with "reflective competence" (p. 1) being a key skill taught progressively in the Leeds University medical school curriculum in the UK. Kennedy et al (2016) reported on a novel place-based learning initiative for law students (Bush Law 101) and explained how embedding collaborative reflection opportunities into the curriculum enabled students to learn how practicing law in regional and rural areas shapes their professional identities. Reflection was also shown to have other benefits for enhancing student employability.…”
Section: Pedagogies Disciplines Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hargreaves (2016), for example, discussed the critical importance of reflection and reflective practice in the context of medical education, with "reflective competence" (p. 1) being a key skill taught progressively in the Leeds University medical school curriculum in the UK. Kennedy et al (2016) reported on a novel place-based learning initiative for law students (Bush Law 101) and explained how embedding collaborative reflection opportunities into the curriculum enabled students to learn how practicing law in regional and rural areas shapes their professional identities. Reflection was also shown to have other benefits for enhancing student employability.…”
Section: Pedagogies Disciplines Referencesmentioning
confidence: 99%
“…Exposing students to work-related knowledge promotes skill development applicable to their future careers (Bandaranaike, 2018;Kennedy et al, 2016), with WIL often acknowledged as providing a point of difference for higher education students to enhance their employability (Hodges & Martin, 2020). WIL and reflective practice enable integration of theory and practice to develop nuanced knowledge and skills in a variety of professions, including teaching (Ramsaroop & Petersen, 2020) and medicine (Hargreaves, 2016).…”
Section: Pedagogies and Assessment For Employabilitymentioning
confidence: 99%
“…156 Place-conscious pedagogy locates education at the point of students' material and physical circumstances, encouraging them to understand where they fit in the world and to be more aware of their accountability to others. 157 In contrast, conventional legal education predominantly occurs in the confines of law schools and by reference to books and lectures, 158 distanced materially, affectively and geographically from the people and places that the laws impact. This is problematic because it contributes to the disjuncture noted by American legal theorist Robert Cover between law and the material acts it enables (eg the sentencing judge from the prison).…”
Section: A the Legal Inheritance Of Institutional Injusticementioning
confidence: 99%